Underlying causes of PM2.5-induced premature mortality and potential health benefits of air pollution control in South and Southeast Asia from 1999 to 2014. (December 2018) - Shi, Yusheng; Zhao, Aimei; Matsunaga, Tsuneo; Yamaguchi, Yasushi; Zang, Shuying; Li, Zhengqiang; Yu, Tao; Gu, Xingfa
Abstract: Quantification of spatial and temporal variations in premature mortality attributable to PM2.5 has important implications for air quality control in South and Southeast Asia (SSEA). The number of PM2.5 -induced premature deaths during 1999–2014 in SSEA was estimated using an integrated exposure-response model based on 0.01° × 0.01° satellite-retrieved PM2.5 data, population density, and spatially and temporally variable baseline mortality data. The results showed extremely high premature death rates in North India and Bangladesh. PM2.5 -induced premature deaths in SSEA increased with small interannual variations from 1999 to 2014 owing to the interannual variations in PM2.5 concentrations. Moreover, four scenarios on the effects of premature deaths by PM2.5 mitigation efforts based on World Health Organization (WHO) air quality guidelines (AQG) and interim targets (ITs) were investigated for each disease and each country during 1999–2014. Four scenarios based on WHO AQG (10 μg/m 3 ), IT-3 (15 μg/m 3 ), IT-2 (25 μg/m 3 ), and IT-1 (35 μg/m 3 ) resulted in 69.3%, 49.1%, 25.4%, and 12.8% reductions compared to the total reference premature deaths (1256, 300), which was calculated using the original PM2.5 datasets. Overall, stroke was the most serious disease associated with air pollution, causing 40% of total premature deaths. Ischemic heart disease was the largest contributor (58%) to the deaths in relatively cleaner air (Scenario 1). The annual rate of change in premature deaths in South Asian countries (India, Bangladesh, and Pakistan) was higher than that in Southeast Asian countries under all scenarios. The results for different scenarios provide insight into the largest health benefits of PM2.5 reduction efforts. Highlights: PM2.5 -induced premature deaths in South and Southeast Asia (SSEA) were estimated. Total premature deaths increased during 1999–2014 with minor interannual variations. Mitigation scenarios explored the effects of PM2.5 reductions on premature deaths. India contributed most to total premature deaths in SSEA. Stroke was the most likely disease to cause premature deaths in polluted air.